Conditional Cash Transfers and Shocks: Evidence from the Philippines - Flaminiano, John Paul (Université d'Ottawa | University of Ottawa, 2019)
We evaluate the impact of the Pantawid Pamilyang Pilipino Program, a conditional cash transfer (CCT) program in the Philippines, on household welfare in the presence of various shocks to household members such as death, illness, loss of employment, business failure, and natural or man-made disasters. Using a regression discontinuity design (RDD), we estimate whether the CCT program induces its beneficiary households to adjust their spending patterns differently from nonbeneficiaries when exposed to shocks. Our estimates show that on average, CCT beneficiary households may allot anywhere from 1.2 to 2 percentage points smaller share of their household income on alcohol and tobacco, relative to non-CCT beneficiary households when exposed to shocks. We find no evidence that CCT beneficiary households adjust their spending on education when exposed to shocks.